Fasting and Postprandial Triglycerides Across Older Adulthood: A Cross-sectional Study. (29th May 2020) - Poindexter, Kara; Sciarrillo, Christina; Hermann, Janice; Emerson, Sam
Abstract: Objectives: Elevated postprandial triglycerides (TG) are a risk factor for cardiovascular disease (CVD). Although some evidence suggests that older adults exhibit greater postprandial TG than younger adults, it is unknown how postprandial lipid tolerance changes across the spectrum of older adulthood. This cross-sectional study examines postprandial TG responses across the spectrum of aging, as well as factors that may modify this response. Methods: We are recruiting individuals into four age categories (age 50–59, 60–69, 70–79, 80–89 years), with an equal number of participants and sex distribution in each group. Participants undergo body composition testing via bioelectrical impedance analysis and complete a 130-item food frequency questionnaire. Participants return to the lab after a 10-hour fast and blood is drawn both before and 4 hours after consumption of a high-fat meal (9 kcal/kg body mass; 73% fat, 26% CHO) to determine fasting and postprandial TG. Results: Thirty participants (50's: n  = 12; 60's: n  = 11; 70's: n  = 4; 80's: n  = 3) have completed the study (total N  = 60). There was no difference ( P  = 0.52) in BMI across age groups (50's: 29.5 ± 5.4 kg/m 2 ; 60's: 29.1 ± 5.5 kg/m 2 ; 70's: 25.9 ± 3.8 kg/m 2 ; 80's: 26.1 ± 1.6 kg/m 2 ). There was also no difference ( P  = 0.68) in body fat (BF%) across age groups (50's: 37.5 ± 7.2%; 60's: 39.53 ± 7.0%; 70's: 43.6 ± 8.2%; 80's: 39.5 ± 18.1%). Similarly, there was no difference ( P  = 0.76) in fasting TG across age groups (50's: 98.8 ± 40.6 mg/dL; 60's: 117.9 ± 83.3 mg/dL; 70's: 105.3 ± 39.7 mg/dL; 80's: 79.7 ± 31.7 mg/dL), nor was there a difference ( P  = 0.74) in 4-hr TG (50's: 162.3 ± 70.8 mg/dL; 60's: 187.5 ± 105.5 mg/dL; 70's: 181.8 ± 89.6 mg/dL; 80's: 130.7 ± 55.1 mg/dL). Lastly, there was no difference ( P  = 0.16) in fruit and vegetable (FV) intake (50's: 4.4 ± 1.9 servings/day (s/d); 60's: 8.2 ± 5.5 s/d; 70's: 6.2 ± 4.6 s/d; 80's: 7.9 ± 2.4 s/d). Conclusions: At this point in the study, it cannot be concluded that there is a significant difference in fasting or postprandial TG across aging strata, possibly due to no differences in BMI, BF%, or FV intake. When complete, this study will provide valuable insight with regard to the impact of aging and other lifestyle factors on postprandial lipemia and subsequent CVD risk. Funding Sources: This project is funded by the Donna Cadwalader Research and Development Grant.